2019
DOI: 10.1007/s00253-019-09680-8
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a competitive ELISA based on bacterium-original virus-like particles of serotype O foot-and-mouth disease virus for detecting serum antibodies

Abstract: Foot-and-mouth disease (FMD) is a highly contagious disease that affects all susceptible cloven-hoofed animals, resulting in considerable economic losses to animal industries worldwide. Numerous categories of enzyme-linked immunosorbent assays (ELISA) have been developed and widely used to evaluate herd immunity. Manufacturing inactivated FMD virus (FMDV) as a diagnostic antigen requires a facility with a high level of biosafety, but this requirement raises concern on viral leakage. In our previous study, bact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Scientists are currently attempting to reform the format of blocking ELISA to detect protective antibodies against FMDV [ 16 , 17 , 18 , 19 , 23 , 24 ]. However, to our knowledge, no comparative studies of different tracers and different antigens using VLPs and P1 have been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scientists are currently attempting to reform the format of blocking ELISA to detect protective antibodies against FMDV [ 16 , 17 , 18 , 19 , 23 , 24 ]. However, to our knowledge, no comparative studies of different tracers and different antigens using VLPs and P1 have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…In the beginning, the solid-phase competition ELISA (SPCE) format used polyclonal antisera as capture antibodies and tracers, with inactivated, purified viruses as antigens [ 17 ]. Later on, polyclonal antibodies were replaced by MAbs as the tracer and capture for large-scale serology [ 18 ], and VLPs replaced inactivated viruses, whose manufacture was limited to BSL3 laboratories [ 18 , 19 ]. A recombinant VP2 subunit protein from the Egyptian SAT2 isolate and a P1 capsid polyprotein of serotype O were also chosen as the diagnostic antigens [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, Brocchi reported that imperfect FMDV type specificity and a different assay standardization for each FMDV serotype are some test limitations of these kits. In addition to monoclonal Ab based kits, a cocktail of polyclonal or monoclonal Abs usage, chimeric antibodies, recombinant Ab production, virus-like particles, or recombinant proteins have also been studied (Ko et al 2009;Yang et al 2017;Cao et al 2018, Ran et al 2019.…”
Section: Discussionmentioning
confidence: 99%